One world, many families - Altergott, Karen (Minneapolis: National Council on Family Relations, 1993)
Contentes: The International Year of the family. Families in transition: America's and the wold's. Nations and States Enacting policy for families. Family policy: a global perspective. Life course issues and family resources. A child is born: conception, fertility and childbearing. Healthy families in healthy cities. Gender issues in global perspective. Husbands, wives and partners. Husbans, wives and partners. Aging in the multigenerational family. Family equality and ethnic Diversity
Keywords: Familia - Sociología Familiar